Sistem Pendukung Keputusan Penilaian Kinerja Guru Terbaik Pada SMA Negeri 1 Telukjambe Barat Menggunakan Metode Analytic Hierarchy Process (AHP) - Arif Siswandi (Teknik Informatika, Universitas Pelita Bangsa, 2020)
In line with this global era, with the rapid development of technology the need for information is needed. Moreover, the information generated contains true, accurate, fast and precise values. Problems that often occur in the teacher performance appraisal process include the subjectivity of decision making, especially if some teachers have responsibilities that are not much different. Decision support system is a decision making process assisted by using computers to help decision making by using certain data and models to solve some unstructured problems. While the Analytic Hierarchy Process (AHP) is a method or tool in multi-criteria decision making using the help of Expert Choice Ver.11 software. the criteria used as a benchmark in determining the assessment of the best teacher performance at SMAN 1 Telukjambe Barat are: Responsibility, Discipline, Diligent, Friendly. From this study found that responsibility is a priority or is preferred at SMAN 1 Telukjambe Barat from the 19 teachers Maya has far better responsibilities and meets the criteria to be the best teacher compared to other teachers. Keywords : Decision Support System (SPK), Analytic Hierarchy Process (AHP), Expert Choice Ver.11., The best teacher